KURIKULUM DAN SISTEM PEMBELAJARAN DI PONDOK PESANTREN SALAF - H. Ali Anwar; Maman Maman (Jurnal Ilmiah Global Education, 2023)
This paper aims to understand the curriculum and learning system in Islamic boarding schools of the Salaf, through textual and contextual understanding. Existing problems are answered through library research. The results showed that the curriculum and learning system at the Salaf Islamic Boarding School were as follows: First, formally no written and documented learning objectives were found, but concretely in the field obtained instructions for instructional learning objectives which ended so that the students had knowledge and noble character. Second, the method used is the wetonan method and the sorogan method. Third, the material he teaches still prioritizes recitation of the yellow book; namely classical religious books as teaching materials, but the focus and attention still refers to the development of morals and self-reliance. Fourth, evaluation. Evaluation of curriculum components has never been carried out. Formally, there are no indicators of success in achieving educational goals, no due diligence on curriculum materials, as well as teaching and learning strategies..